PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS QUANTUM TEACHING MATERI BANGUN RUANG SISI DATAR KELAS VIII SMPN 4 KOTO BARU - Auliya Rahman; Aryo Andri Nugroho; Fenny Roshayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The research aims to determine the effect of the problem-based learning model assisted by audio-visual media on students' critical thinking skills and learning outcomes. This type of research is a quasi-experimental research or quasi-experimental research with the Nonequivalent Group Pretest-Posttest Design. The population in this study were students of class VI SD Negeri Tulis 01, Tulis District, Batang Regency, totaling 42 students who were divided into two classes, namely the experimental class and the control class. The instrument in this study used tests of critical thinking skills and student learning outcomes in the form of pretest and posttest questions. Data analysis techniques were performed using the Independent Sample t-test to test the hypothesis. Based on the research, it can be concluded that there is an increase in learning outcomes through the pretest and posttest in the experimental and control classes and there is an increase in attitudes indicating increased critical thinking skills. This means that there is an effect of the use of audio-visual-assisted problem-based learning models on students' critical thinking skills and student learning outcomes. There is a relationship between critical thinking skills and student learning outcomes.